Utilización de lepidópteros como bioindicadores para el diagnóstico de ecosistemas en la Microcuenca Shilcayo - Cárdenas Saavedra, Gina (2008)
This research project entitled "Use of Lepidoptera as biomarkers for the diagnosis of ecosystem Microcuenca Shilcayo" was run along the watershed; whose objective was to collect and evaluate three lepidopteran sample units to be used as biomarkers for the respective diagnosis while mapping spatial distribution function of ecosystem types studied. Evaluations were carried out from July 2007 to January of this year; due to inclement weather occurred. The results indicate that the overall composition of the community of Lepidoptera is 1017 individuals belonging to 42 species and community composition assessed lepidopteran between stations is 282 individuals belonging to 21 species in Wingos station in the station Pukalluichu 331 individuals belonging to 28 species were recorded in the third season and called Takiwasi 404 individuals belonging to 32 species were quantified. It was concluded that the conservation of Lepidoptera is closely linked with that of the ecosystems in which they fulfill their life cycles, they reflect the state of the three areas are assessed; Wingos sector has been defined as fully involved forest / degraded area without agricultural use Pukalluichu Residual Forest sector associated Takiwasi secondary forest and primary forest sectors concerned and intervened. Besides maps spatial distribution of biomarkers based on elaborate ecosystem types, these tools will facilitate learning and identifying the most representative species of Lepidoptera in each area.